A Review of Personality and Motivation - Rani, Usha (Innovative Research Thoughts, 2018)
'The influence of personality on motivation and organisational behaviour,' is the subject of this review of the literature. Research topics included whether or not personality affects motivation and behaviour in the workplace as well as whether or not personal characteristics influence workplace behaviour. it consulted previously “published sources from popular journals like the Journal of Applied Psychology, Personality and Social Psychology, the Academy of Management Review, and Organizational Behaviour. Next, a review of personality theories was carried out, including the characteristics theory as well as ideas from psychoanalysis, the humanistic perspective and social cognition. personality has an impact on motivation via emotional stability, degree of hostility, and the extrovert or introverted traits of employees. Organizational tolerance, work atmosphere, and work ethics are all influenced in part by an individual's personality. Managers should take personality into account when they are trying to motivate their employees and improve organisational behaviour in the workplace.